EU2'S REGIONAL ECONOMIC RECOVERY SOLUTIONS UNDER THE GLOBAL CRISIS - Ionescu Romeo (European Regional Science Association (ERSA), 2011)
The paper deals with the necessity to implement sub-regional specific solutions in order to achieve the economic recovery. EU2 countries (Bulgaria and Romania) have the same political and economic past, present and future and the same challenges to face. This is why both countries are analysed together in order to present the disparities between the real economic environment and the economic recovery measures implemented. The punt is high, because these latest Member States would be transformed into a good practice example for other member and candidate countries. Unfortunately, the reality is different. The analysis is focused on the anti-crisis programs from EU2 and their experience with the international financial institutes. The analysis is supported by Eurostat and official databases in order to describe the symmetrical shock to asymmetrical implications on the economy. The conclusions of the analysis can be resumed to the following: the global crisis affected powerfully the latest two EU member states; the financial regulation represents a critical area to create a sustainable and efficient financial system; the real target for Romania and Bulgaria is to save themselves from the national bankruptcy; the popular pressure on the policymakers increased and the economic recovery implemented plans are not able to support the economic recovery in both countries. The analysis and the conclusions of the paper are followed by pertinent statistical tables and diagrams.
Keywords: 330